2011
DOI: 10.3109/15412555.2011.611200
|View full text |Cite
|
Sign up to set email alerts
|

Asthma, Chronic Obstructive Pulmonary Disease, and Mortality in the U.S. Population

Abstract: In this analysis, subjects who report coexisting asthma and COPD have a higher risk of obstruction on spirometry and a higher risk of death during follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
83
3
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 28 publications
8
83
3
4
Order By: Relevance
“…Also more airway complications needing oral steroids, antibiotics or hospitalizations were seen in patients with ACOS compared with those with asthma and COPD alone [De Marco et al 2007;Gibson and Simpson, 2009]. In a large study on self-reported asthma or COPD, the combination of self-reported asthma and COPD was associated with increased overall mortality [Diaz-Guzman et al 2011].…”
Section: Prognosismentioning
confidence: 99%
“…Also more airway complications needing oral steroids, antibiotics or hospitalizations were seen in patients with ACOS compared with those with asthma and COPD alone [De Marco et al 2007;Gibson and Simpson, 2009]. In a large study on self-reported asthma or COPD, the combination of self-reported asthma and COPD was associated with increased overall mortality [Diaz-Guzman et al 2011].…”
Section: Prognosismentioning
confidence: 99%
“…COPD-betegek esetében az ACOS megjelenése 10-55%-ra tehető, attól függően, hogy milyen diagnosztikus kritériumok alapján készült a vizsgálat. Megfigyelhető, hogy az életkor előre-haladtával az ACOS prevalenciája emelkedik [8][9][10], míg a populáción belüli átlagos megjelenése 2%-ra tehető [11,12]. A magas prevalencia ellenére a betegek jelentős része eddig kizárásra került a kontrollált, kettős vak, illetve prospektív klinikai vizsgálatokból és az inhalatív gyógyszerek hatásossági vizsgálataiból.…”
Section: öSszefoglaló Közleményunclassified
“…Furthermore, the prevalence of ACOS (3.2%) was lower than COPD (6.0%) or asthma alone (5.6%) in the United States (15), whereas the percentage of patients visiting emergency departments was high for ACOS than for COPD alone in Korea (16). This is associated with utilization of a large proportion of medical resources and, in turn, leading to higher healthcare costs because hospitalizations account to the largest expenditure, thereby imposing heavy economic burdens on patients (17). Previous research conducted in urban China, 2010, 2012, and 2013 China National Health and Wellness and internet-based Survey (NHWS) revealed a high incidence of ACOS in urban China, which was associated with the greatest co-morbidity burden (P<0.05) compared with asthma and COPD along with worse healthcare outcomes (18).…”
Section: Introductionmentioning
confidence: 99%